ACTIVATION OF ADAPTOGENESIS AND BIORESOURCE POTENTIAL OF CALVES UNDER THE CONDITIONS OF TRADITIONAL AND ADAPTIVE TECHNOLOGIES - Semenov Vladimir Grigoryevich; Baimukanov Dastanbek Asylbekovich; Kosyaev Nikolay Ivanovich; Alentayev Aleidar Saldarovich; Nikitin Dmitry Anatolyevich; Aubakirov Khamit Abilgaziyevich (Scientific Journal of Pedagogy and Economics, 2019)
For the first time, the influence of the biological stimulators of the new generation, polystim and PV1, on the growth and development of calves under the conditions of traditional growth technology and in premises of lighter type of the adaptive technology (individual houses and pavilions on the open area) and on the quality of young stock meat has been studied. The possibility of activating the adaptive processes and increasing the resistance of the organism of such animals under the influence of these biostimulators to low temperatures of the habitat for protein-carbohydrate-vitamin metabolism, the function of the hematopoietic organs and the buffer system is established. The tested preparations activated the growth and development of calves, reduced the incidence of respiratory organs and gastrointestinal tract. The possibility of correction of cellular and humoral factors of nonspecific resistance of the calf organism with the help of polystim and PV-1 during the winter period when growing according to traditional technology and in premises of light type has been experimentally proved. Activation of the bioamine spectrum of the blood components was revealed due to manifestations of response reactions from the sympatho-adrenal, serotonergic and histaminergic systems of the calves organism depending on different growing conditions. The quality of meat of the animals, which were injected with biostimulators, did not differ in organoleptic, biochemical and physicochemical parameters from those obtained without the use of stimulators, which indicates its ecological safety and biological fullness.